ON SOME SPECIFIC FEATURES OF HIGH-FREQUENCY SOUND DISPERSION IN A SOLUTION WITH A PECULIAR POINT - Sabirov, L; Semenov, D; Begaliyev, H (Scientific practical conference, 2026)
Aqueous solutions of methyl derivatives of pyridine with concentrations 0.06 to 0.08 mole fraction (MF) at the normal air pressure and temperature t0 ≈ 70oC have a minimum of thermodynamic stability [1] (a peculiar point in the temperature−concentration phase diagram) and thus are convenient for studying structural transformations in the vicinity of the peculiar point.